2016
DOI: 10.1055/s-0036-1594239
|View full text |Cite|
|
Sign up to set email alerts
|

Skull Base Invasion Patterns and Survival Outcomes of Nonmelanoma Skin Cancers

Abstract: Report routes of skull base invasion for head and neck nonmelanoma skin cancers (NMSCs) and their survival outcomes. Retrospective. Ninety patients with NMSC with skull base invasion between 2004 and 2014. Demographic, tumor characteristics, and treatments associated with different types of skull base invasion and disease-specific survival (DSS) and overall survival (OS). Perineural invasion (PNI) to the skull base occurred in 69% of patients, whereas 38% had direct skull base invasion. Age, histology, orbital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…We have described skull base invasion patterns and survival outcomes of nonmelanoma skin cancers and found that the route and extent of skull base invasion significantly affect disease-specific and overall survival. 10 For these patients, the success of initial surgical treatment relies heavily on accurate clinical judgment of the magnitude of disease spread to achieve resection with negative margins. 11 Magnetic resonance imaging (MRI) can delineate large nerve perineural spread classified according to the degree of skull base involvement 12 and is valuable for determining zonal classification: peripheral (zone 1), skull base (zone 2), and central (zone 3).…”
mentioning
confidence: 99%
“…We have described skull base invasion patterns and survival outcomes of nonmelanoma skin cancers and found that the route and extent of skull base invasion significantly affect disease-specific and overall survival. 10 For these patients, the success of initial surgical treatment relies heavily on accurate clinical judgment of the magnitude of disease spread to achieve resection with negative margins. 11 Magnetic resonance imaging (MRI) can delineate large nerve perineural spread classified according to the degree of skull base involvement 12 and is valuable for determining zonal classification: peripheral (zone 1), skull base (zone 2), and central (zone 3).…”
mentioning
confidence: 99%
“…Although current guidelines recommend considering adjuvant RT for extensive or clinical PNBCC, the management of histologic PNBCC has remained undefined. 9,12,13,31 Our meta-analysis demonstrated statistical equivalence between Surg + RT and surgery alone for histologic PNBCC with an overall excellent local control and cancer-specific survival.…”
Section: Discussionmentioning
confidence: 72%
“…giant BCC, orbital wall invasion, or skull base invasion). 2,6,10,12,17,24,29,31,33–56 Given the propensity for basosquamous disease to act more like SCC with a higher risk of lymph node involvement and metastasis, basosquamous carcinoma studies were not included and cases were excluded whenever possible. 57 No randomized, controlled trials or systematic reviews were identified.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation